1997
DOI: 10.1080/000368497326868
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the yen-dollar real exchange rate and the US-Japan real trade balance

Abstract: This paper employs cointegration and error correction models to examine the dynamics of the yen-dollar real exchange rate and the US-Japan real trade balance. It uses quarterly data from 1973.I-1993.IV. The unit root tests reveal non-stationarity in both the variables. The ADF test fails to affirm any long-run association between the yen-dollar real exchange rate and the US-Japan real trade balance. Also, there is evidence of bidirectional short-run Granger causality between these two variables with mutual fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…The list includes Briguglio (1989), Tegene (1991), Buluswar et al (1996), Rahman et al (1997), Nachane and Ranade (1998), Miljkovic (2000), Bahmani-Oskooee (2001), Kyereme (2002) and Berument and Dincer (2005). 2 For a comprehensive study and estimates of the Marshall-Lerner condition see Bahmani-Oskooee and Niroomand (1998).…”
Section: The Models and The Methodsmentioning
confidence: 99%
“…The list includes Briguglio (1989), Tegene (1991), Buluswar et al (1996), Rahman et al (1997), Nachane and Ranade (1998), Miljkovic (2000), Bahmani-Oskooee (2001), Kyereme (2002) and Berument and Dincer (2005). 2 For a comprehensive study and estimates of the Marshall-Lerner condition see Bahmani-Oskooee and Niroomand (1998).…”
Section: The Models and The Methodsmentioning
confidence: 99%
“…These studies have found a significant relationship between the trade balance and the EXR. On the other hand, studies by Greenwood (1984), Mahdavi & Sohrabian (1993), Rahman et al (1997) and Duasa (2007) have found rather weak empirical evidence on the relationship between the EXR and the X and M flows. Based on these empirical findings, inconclusive evidence exists as to whether the EXR are statistically significant in determining the X and M flows.…”
Section: Theoretical Framework and Methodologymentioning
confidence: 99%
“…Various papers investigated whether there is a so-called "J-curve", with devaluations leading to a short-run deterioration of the TB but a long-run improvement (see Bahmani-Oskooee, 1985;Rahman, Mustafa, and Burckel, 1997;Himarios, 1989;Rose and Yellen, 1989;Briguglio, 1989;Noland, 1989;Rose, 1990;Berument, 2005), with mixed results. Most studies use bilateral aggregate data (see, e.g., Boyd et al, 2001;Lal, and Lowinger, 2002;Onafuwora, 2003;McDaniel, and Agama, 2003;Fullerton and Sprinkle, 2005;Bahmani-Oskooee et al, 2006;Narayan, 2006;Bahmani-Oskooee, and Hegerty, 2011;Dash, 2013;Costamagna, 2014), again providing mixed evidence.…”
Section: Literature Reviewmentioning
confidence: 99%